Karakteristik Kimia dan Organoleptik Abon Jamur Tiram Berdasarkan Jenis Kemasan dan Lama Penyimpanan - Guntur Prasetyo; Nurhidajah Nurhidajah; Nurrahman Nurrahman (Jurnal Pangan dan Gizi, 2018)
Oyster mushroom (Pleurotus ostreatus) is one of the popular mushroom, It tastes delicious and full of nutrients, high protein and low fat. Oyster mushrooms are easily damaged because moisture content high enough around IU 86,6% by understanding the content. Iit is necessary to prolong the process of keeping the oyster mushroom. The processing of oyster mushrooms into oyster mushrooms floss. This research aims to know the influence of the type of packaging and retention levels of TBA, moisture content, and the organoleptic of oyster mushrooms. This study used a randomized complete design of factorial which is composed of two factors, the first factor is the type of packaging Polypropilen (PP) and Polyetilen (PE) with a thickness of 0,5 mm  and long storage (0 days, 10 days, 20 days and 30 days) in room temperature. The results of statistical tests obtained that kind of old packaging and storage has no effect to the levels of TBA, moisture content, and organoleptic. Level of oyster mushroom floss’s TBA at the end of saving times on packaging of PP is 1,737 mg malonaldehid/kg of  sample and PE 1,420 mg malonaldehid/kg of samples. The values are still under the SNI 01-2352-1991. Moisture content of oyster mushrooms floss on the end saving times on packaging of PP is 1,169% and PE 1,157%. These values are still under the SNI 01-3707-1995. Organoleptic results until 30 days showed not influence of flavours, texture and taste. Oyster mushrooms floss has attracts  tastes, dry textures a bit crispy and taste good.